Sports and entertainment marketing - Kaser, Ken; Oelkers, Dotty Boen (South-Western/Cengage Learning, 2016)
Popular sports and entertainment topics continue to be the foundation for teaching marketing concepts in this expanded, updated edition. Throughout the book, each marketing function is highlighted with an icon to indicate how it is used in the marketing process. The text addresses current trends in social media as it relates to promotion, and also covers math functions that would be needed in marketing.